Obstetric ultrasound in the first trimester: Review of recommendations and limitations (Research, Society and Development, 2025)
This article aims to review the current recommendations and limitations of obstetric ultrasound in the first trimester, emphasizing its relevance for early diagnosis, maternal-fetal monitoring, and anomaly screening. A narrative literature review was conducted using the BVS and PubMed/MEDLINE databases, in addition to analyzing guidelines from SOGIRGS, the Brazilian Medical Association, and the Ministry of Health. Articles published in the last five years, in Portuguese, English, and Spanish, were included. The results show that early ultrasound is essential for the diagnosis and prediction of pregnancy outcomes, with high accuracy for detecting major malformations between 11 and 14 weeks of gestation. However, limitations such as operator dependence, technological variability, and the risk of false diagnoses highlight the need for caution. It is concluded that the exam is indispensable in prenatal care but should be interpreted as a complementary tool, with standardized protocols, professional training, and continuous updates of clinical guidelines.